Uma proposta para o ensino de progressões aritméticas e geométricas na segunda série do ensino médio utilizando a sala de aula invertida - Ramos, Victor José Dias (2024)
Arithmetic and Geometric Progressions are, in general, finite or infinite numerical sequences established by a ratio. This content, according to the BNCC (Brasil, 2018), is approached in all High School, with emphasis on the second year of High School. The methodology research used was applied descriptive qualitative, and the methods for data collection were documentary research and data survey. This thesis aims to investigate hybrid teaching and active methodologies, emphasizing and enhancing flipped classrooms. It also inquires how this teaching modality can support the teaching-learning process of the concepts of arithmetic and geometric progressions. Furthermore, it is proposed that the students reflect on their passive performance (very common in most current schools), engaging them in their learning process, allowing a greater interest in the class as a whole, and fostering students to become more active. When the focus is on the teacher's role, the proposal is that he/she should have a more innovative concept being able to explore the skills of the students and assumed a role as a facilitator and guide. The results revealed that the use of these resources had a motivating effect on the students, providing more attractive and dynamic classes